Is Research on Transgender Children What It Seems? Comments on Recent Research on Transgender Children with High Levels of Parental Support. - Schumm, Walter R.; Crawford, Duane W. (Linacre Quarterly, 2020)
Recent research on transgender children who have had support from their parents for their transitioning has concluded that their mental health is virtually no different than that of nontransgender children. Such research has been extensively cited, over 370 times in the past three years. Most of the hundreds of reviews received the stated results of the studies with little caution. However, the research featured numerous statistical errors and omissions, the implications of which would likely lead neutral observers to conclude that the mental health of transgender children, even when supported by their parents, was poorer than that of the groups of control children. In particular, levels of anxiety as reported by both parents and their transgender children appear to be significantly higher, and the transgender children's reports of self-worth appear to be significantly lower. Although reports regarding depression are not as significantly different, the effect sizes were generally in a similar direction as the other outcomes, being less favorable for the transgender children. Such issues highlight the need for careful examination of statistical research, even when published in highly regarded medical journals. As with other research, findings from the early stages of controversial research may often be premature. Further research is needed to explore factors underlying these results. Summary: Some scholars have believed that if transgender children were supported by their parents before the children reached puberty, the generally higher rates of mental illness experienced by many transgender persons might be prevented or alleviated. Dr. Kristina Olson of the Department of Psychology at the University of Seattle was the first scholar to have studied groups of transgender children who were being supported by their parents and to have compared them to a control group of children and to siblings of the same transgender children. Her conclusion was that there were minimal, if any, differences in anxiety, depression, and self-worth among the groups of children; her research has since been cited extensively as having found just that. We reanalyzed her raw data and found that, to the contrary, the transgender children, even when supported by their parents, had significantly lower average scores on anxiety and self-worth. Often, a significantly higher percentage of transgender children, compared to controls, featured preclinical or clinical levels of anxiety. Parental support of transgender children may temporarily reduce levels of poor mental health for some transgender children, but it does not appear to eliminate those problems for all transgender children. Our findings should serve as a warning against accepting research at a surface level, which can lead to acceptance of invalid information and pursuit of ineffective interventions.